Efisiensi Penggunaan Faktor Produksi Usaha Tani Wortel Di Kecamatan Bandar, Kabupaten Aceh Tengah - Irwan Irwan; Buni Amin (Jurnal Agripet, 2007)
ABSTRACT. The prospect of carrot farmusines in Bndar subdistrict, Aceh Tengah District very good. Beside of agroclimatology in vegetable production center, can be positive impact to the income farmer increasing, good nutrition of the people, chance of labor and agribusiness. The commodity market fot this commodity very big, but the price still lower. This condition occurred because of allocation production factor in this farbussines not efficient.